STUDY COMPARASI TERAPI SLOW DEEP BREATHING DAN GUIDED IMAGERY RELAKSASI DALAM MENURUNKAN SKALA NYERI PASIEN CEDERA KEPALA RINGAN PASCA PEMBERIAN ANALGETIK DI IGD - mariza Elsi Elsi (Jurnal Ipteks Terapan, 2019)
The main problem head injury patients are pain, when someone is experiencing pain are non-pharmacological strategies are as good as pharmacological strategies that can be offered to clients, some non-pharmacological interventions do not require instruction but an initiative of the nurses. Terapy Slow deep breathing is breathing with a frequency of less than 10 beats per minute and long inhalation phase can increase oxygen supply to the brain and decrease the metabolism of the brain so that the brain needs oxygen decreases. Guided imagery is an attempt to create the impression in the mind and then concentrate on the impression that gradually lowers the client's perception of pain. The purpose of this study was to compare the terapy slow deep breathing and guided imagery to decrease the patient's pain scale of mild head injury.This research method was Quasi-Experimental use a pretest-posttest. slow deep breathing (intervention 1) of the 17 respondents and guided imageri (intervention 2) 17 response, the assessment carried out six hours after patients received pharmacological treatment, size scale use numeric rating scale (NRS) The result of slow deep breathing therapy is more effective to reduce the pain scale in patients with mild head injury in Emergency Room Hospital Ulin Banjarmasin with p = 0.001, be compared terapy guided imagery relaxation with p = 0.264